2015
DOI: 10.1515/cclm-2015-0876
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of the (-2)proPSA and evaluation of the evidence: a systematic review

Abstract: Background: Diagnostic studies usually provide important information about the analytical and diagnostic performances. We investigated the clinical utility of (-2) proPSA in identifying patients with prostate cancer (PCa). Methods: We performed electronic searches in five databases as well as a list of reference literature. Studies were included if they evaluated the diagnostic accuracy of (-2)proPSA in men with PSA value ranged from 2.0 to 10 μg/L. We also analyzed data about total PSA (tPSA), %(-2)proPSa, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Interestingly, a low possibility of PCa outcome on biopsy is supplementary to small PHI results, while an elevated possibility of PCa outcome on biopsy is directly related to elevated PHI. Different medical considerations or family history of PCa are dominant factors in the management process as it relates to the appropriate PHI value [70,72,73].…”
Section: Prostate Health Indexmentioning
confidence: 99%
“…Interestingly, a low possibility of PCa outcome on biopsy is supplementary to small PHI results, while an elevated possibility of PCa outcome on biopsy is directly related to elevated PHI. Different medical considerations or family history of PCa are dominant factors in the management process as it relates to the appropriate PHI value [70,72,73].…”
Section: Prostate Health Indexmentioning
confidence: 99%
“…The Phi test is a better tool for clinically significant PCa identification, than its individual components [5]. A systematic review by Pecoraro et al [20] that included 17 studies with 6,912 patients on Phi concluded that Phi increases the specificity for PCa detection [20]. For p2PSA the authors reported AUC ranging from 0.51 to 0.62, highlighting a better performance for %p2PSA (AUC from 0.63 to 0.78) and Phi (AUC from 0.67 to 0.78) [4,10,19,21,22].…”
Section: Figure 1 Roc Curve Analysismentioning
confidence: 99%
“…PHI testing is approved for men at least 50 years old with normal DRE results and PSA values within the gray zone of 4–10 ng/ml. A meta-analyses reported that PHI has higher diagnostic accuracy rates than other PSA derivatives [54]. In addition, studies have demonstrated that these biomarkers have utility in predicting aggressive PCa (defined as Gleason score ≥7) [53▪▪,5558].…”
Section: Determining the Need For Prostate Biopsymentioning
confidence: 99%